Obligations Erga Omnes and International Public Order after the Decision in the Belgium v. Senegal Case - Kamiyama, Marcel Ichiro Bastos (Revista dos Estudantes de Direito da Universidade de Brasília, 2014)
This paper analyses the role of erga omnes obligations in contemporary Public International Law from the standpoint of relevant conventions and case-law. In this regard, the movement from bilateralism to community interest in the international legal system was confirmed by the International Court of Justice in its recent and emblematic case between Belgium and Senegal, in which the UN Convention against Torture was held to establish a public legal interest inter partes in the implementation of its provisions. Hence, the utility of the notion of erga omnes (partes) obligations with respect to standing before the Court was affirmed. It is sustained that, pursuant to this obiter dictum, international litigation on behalf of public interest is an irrevocable possibility, with the international judiciary, especially the International Court of Justice, playing an important part in the consolidation of the international legal public order.